2016
DOI: 10.1111/aji.12599
|View full text |Cite
|
Sign up to set email alerts
|

Foetal Ureaplasma parvum bacteraemia as a function of gestation‐dependent complement insufficiency: Evidence from a sheep model of pregnancy

Abstract: Ureaplasma bacteraemia in vivo was confined to early preterm lambs with low complement function, but Ureaplasma infection itself did not diminish complement levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In accordance with several earlier studies ( 12 , 33 35 ), intra-amniotic infection following intra-amniotic UP administration was confirmed by the presence of UP in amniotic fluid during Cesarean section. No endogenous UP was detected in the amniotic fluid prior to inoculation (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…In accordance with several earlier studies ( 12 , 33 35 ), intra-amniotic infection following intra-amniotic UP administration was confirmed by the presence of UP in amniotic fluid during Cesarean section. No endogenous UP was detected in the amniotic fluid prior to inoculation (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…To investigate whether N-9-induced cervical epithelial challenge predisposes to ascending infection during pregnancy, we examined the magnitude and frequency of ascending bacterial infection following experimental vaginal inoculation of UP. UP was chosen as this is the most frequently isolated bacterial species associated with PTB 36 and the UP strain (HPA5) utilised has extensively been used in sheep models of intrauterine infection [37][38][39] .…”
Section: Resultsmentioning
confidence: 99%
“…Viable bacteria were quantified by 10-fold dilution (series of 15 µL in 135 µL) of inoculation stocks, vaginal flushes or amniotic fluid samples in USM in sterile 96-well plates (Elkay, Basingstoke, UK), sealed with clear adherent sealing film (Elkay, Basingstoke, UK) following incubation at 37°C for 48 h. For post-infection quantification, all values are calculated for bacterial load in the 15 µL of amniotic fluid or vaginal flush, for inoculating stocks values were calculated per mL of stock. A large-scale stock for inoculation was prepared by collecting mid-log phase growth UP after overnight incubation as previously described for experimental in utero pregnant sheep studies 39 . Inoculating stock was divided into 200 µL aliquots and sufficient aliquots were freshly thawed for the required number of mice to be infected in each batch of pregnant Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic intrauterine Ureaplasma exposure appears to downregulate the host response to acute LPS exposure in the preterm sheep model [ 47 ]. Yet, the presence of Ureaplasma may be a function of prematurity as Kemp et al found that host bactericidal activity was directly correlated to gestational age, and the bactericidal activity appeared related to functional complement activity [ 48 ].…”
Section: Discussionmentioning
confidence: 99%